1998
DOI: 10.1152/ajplung.1998.275.1.l80
|View full text |Cite
|
Sign up to set email alerts
|

Differential regulation of glutathione by oxidants and dexamethasone in alveolar epithelial cells

Abstract: We studied the regulation of GSH and the enzymes involved in GSH regulation, γ-glutamylcysteine synthetase (γ-GCS) and γ-glutamyl transpeptidase (γ-GT), in response to the oxidants menadione, xanthine/xanthine oxidase, hyperoxia, and cigarette smoke condensate in human alveolar epithelial cells (A549). Menadione (100 μM), xanthine/xanthine oxidase (50 μM/10 mU), and cigarette smoke condensate (10%) exposure produced increased GSH levels (240 ± 6, 202 ± 12, and 191 ± 2 nmol/mg protein, respectively; P < 0.00… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
26
1

Year Published

1999
1999
2018
2018

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 43 publications
(32 citation statements)
references
References 28 publications
5
26
1
Order By: Relevance
“…In this study, changes in glutamylcysteine ligase mRNA were not found, but the airways were sampled after 12 h of hyperoxia, and earlier time of induction would not have been detected. However, other interacting components of the glutathione-antioxidant system, including ␥-glutamyltransferase, glutathione peroxidases, and glutathione reductase, were not induced in this study, or in previous in vitro studies of primary human bronchial epithelial cells and bronchial epithelial cell lines exposed to hyperoxia (15,24,(49)(50)(51). Other data support that upregulation of glutathione antioxidant systems are not requisite for defense against hyperoxia (25,38,52,53).…”
Section: Discussionsupporting
confidence: 63%
“…In this study, changes in glutamylcysteine ligase mRNA were not found, but the airways were sampled after 12 h of hyperoxia, and earlier time of induction would not have been detected. However, other interacting components of the glutathione-antioxidant system, including ␥-glutamyltransferase, glutathione peroxidases, and glutathione reductase, were not induced in this study, or in previous in vitro studies of primary human bronchial epithelial cells and bronchial epithelial cell lines exposed to hyperoxia (15,24,(49)(50)(51). Other data support that upregulation of glutathione antioxidant systems are not requisite for defense against hyperoxia (25,38,52,53).…”
Section: Discussionsupporting
confidence: 63%
“…The most prominent finding of the current study, the increase in antioxidants in the alveolar compartment, may provoke the speculation that antioxidant metabolism in [31] found that both glutathione and c-glutamylcysteine synthetase levels increase in alveolar type II cells after oxidant treatment. This may be induced by activation of redox-sensitive transcription factors, such as nuclear factor-kB and activator protein-1, which are involved in regulation of antioxidant genes.…”
Section: Discussionmentioning
confidence: 65%
“…As described previously (Rahman et al, 1998), smoke extract "strength" was evaluated by measuring nitrite using the Griess reaction (Bishop-Bailey et al, 1997) to ensure continuity between batches. In all experiments, nitrite levels in 100% cigarette smoke extract was between 12 and 16 M.…”
Section: Methodsmentioning
confidence: 99%